Research and trends in the studies of native & non-native speaker teachers of languages: a review on selected researches and theses - Jusoh, F.S.; Alias, N.; Siraj, Saedah; Darusalam, G. (2012)
Recruiting and employing native speaker teachers of English Language (NST) in non-native speakers’ context are widely practised in countries which learn and use the target language taught by the native speaker teachers (NST) as either as a second or a foreign language. This paper reviews selected journals and thesis on the issues of Native and Non-native Speaker Teachers (NST & NNST). It covers on students’, as well as the Native and Non-Native Speaker Teachers’ (NNST) self-perceptions and attitudes. This review discovers almost the same pattern of students’ attitudes and perceptions towards native speaker teachers. Most studies reviewed indicate that most of the non-native learners of the target language have positive attitude towards native speaker teachers. They view native speaker teachers as the model of the target language learnt and believe that the native speaker teachers could provide a great example in learning pronunciation and speaking skill. In addition, this review also identifies that learners believe that their non-native teachers are compatible in teaching the language as they have experienced in being second language learners. As such, they are more empathic and are able to apply the suitable teaching approaches for the learners in learning the language. In contrast, the learners view their non-native speaker teachers are weak in teaching oral communication skills as they believe that in order to learn communication skills, native speaker models are required. However, the learners still prefer the collaborative teaching of native and non-native speaker teachers of the language when learning the target language. This is because they take the native speaker teachers as their model to learn the language and the non-native speaker teachers as their interpreter. Nonetheless, this review also finds that learners value both native and non-native teachers of the language.